Development of prototype smart helmet and blind spot detection for motorcyclist safety features - Mohd Hussin, Umi Nuratiqah; Lam, Hong Yin; Sim, Sy Yi; Mustafa, Farahiyah; Ishak, Maizul (FAZ Publishing, 2020)
Motorcycle safety concerns many aspects of vehicle and equipment design as well as operator skill and training that are unique to motorcycle riding. This project focus on the development of prototype smart helmet and blind spot detection features for motorcyclist safety system. The main objective of this work is to reduce the blind spot area for motorcyclists. The developed system are capable of measure appropriate distances (~ 10 cm to 50 cm) of insecurity among motorcyclists and vehicle behind by means of ultrasonic sensors and vibrator motor. The ultrasonic sensor play a role to detect any vehicle from behind the motorcyclist and system will alert the rider through the vibrator motor, LEDs and buzzer that install at the helmet as a warning to the rider about the range of insecurity. The system employed Arduino UNO as the main processing unit to control all the connectivity components. OLED display are also connected to the Arduino UNO mounted in front of the rider for displaying the distance detected by the ultrasonic sensor. Wireless transceiver module is use to serve as a data transmitter and receiver in which transmitted data collected by ultrasonic sensor will wirelessly transmit to the helmet node which is the receiver unit. In conclusion, this developed prototype project work are able to provide better solution for motorcyclist safety features in order to reduce the probability of accidental rate.